A Case of Atorvastatin-Associated Necrotizing Autoimmune Myopathy, Mimicking Idiopathic Polymyositis - Ayushi Dixit; Adriana Abrudescu (Case Reports in Rheumatology)
Statin-induced necrotizing autoimmune myopathy (SINAM) is a rare side effect of statin use which manifests as progressive muscle weakness. Because statins are a widely prescribed medication for coronary artery disease, hyperlipidemia, and many other diseases, many patients are at risk of developing SINAM or one of the many other statin-induced myopathies. Due to identification of an antibody specific to this disease, we were able to diagnose SINAM in a patient whose symptoms had progressed to the extent that they were debilitating. Our case describes SINAM in a patient undergoing treatment with a statin for an extended period of time, diagnosis of the disease process, treatment, and resolution of symptoms.